Evaluating the effect of fennel soft capsules on the quality of life and its different aspects in menopausal women: a randomized clinical trial - Fatemeh Rahimi Kian; Reza Bekhradi; Roja Rahimi; Parvin Golzareh; Abbas Mehran (Nursing Practice Today, 2017)
Background & Aim: Menopause is one of the natural phases of women’s life. At this phase, due to the large fluctuations in hormones, undesirable physical, mental and sexual symptoms would occur that have negative effects on the quality of life of women. Due to the side effects of hormonal therapy, many women would prefer complementary medicine and especially herbal medicine. The present study was conducted to evaluate the effect of fennel on the quality of life in menopausal women.